A PROCESS-GENRE APPROACH TO TEACHING WRITING ANARRATIVE TEXT IN A CREATIVE WRITING CLASS: A CASESTUDY IN A PRIVATE UNIVERSITY IN EAST NUSA TENGGARA,INDONESIA - Fety Surfaifel, - (2024)
This case study was designed to find out (1) how the Process-Genre Approach assists EFL learners in producing a good text and (2) What the EFL learners say about the process-genre approach. The study involved 30 second-year regular class students of the English education program. It was conducted in the second semester for 11 meetings in the 2022/2023 academic year. The data were collected from participant observation field notes, transcripts of the students' interviews, and documentation of the students' texts. Then, the observation and the interview were analyzed by using thematic analysis. In the meantime, the students' written texts were analyzed by using assessment criteria proposed by Emilia (2016) and Rose (2012). The results show that a Process Genre Approach can help develop the student's creative writing in producing the narrative text where the study applied teaching stages of PGA, the basic principles of GBA such as explicit teaching, group work, and a recursive process of creative writing that includes the lecturer and peer feedback. In addition, the results also show a good development of the students' texts using the assessment criteria. It also shows good students' control of the schematic structure of a narrative genre with its linguistic features, followed by their control of creative writing skills such as fluency, flexibility, clarity, originality, and elaboration that can indicate good practice of narrative. The study recommends that the process genre approach can help tertiary students in different contexts in Indonesia to prepare their work on creative assignments. Another recommendation is that explicit teaching should allow the students to achieve a similar understanding and competence in creative writing.